Wednesday

April 16, 2014

April 16, 2014

Posted by **DANIELLE** on Monday, January 8, 2007 at 3:14pm.

2x+y=5 y=5-2x

3x-y=10 -y= 10- 3x

I have substituted y= 5-2x into the second equation

3x- (5-2x)=10

5x+5=10

x=1

Here I got lost and dont know what to do next in plotting the graph. Thanks for you help

**Related Questions**

algebra - Can someone please help me with this math problem? Thanks. Let g(x)=x^...

Grade 10 Math - I've missed quite alot of school because I was sick and when I ...

Algebra - Here is the problem: Given f(x)=-x^3+3x^2-2x+6, find f(-1), f(0), and ...

algebra - Divide (3x^3-x^2+8x-9) by (x-1) Please help! I'll show you how this ...

Algebra - How do I work this correctly? I know the answer is 7 but I am doing ...

algebra - I am totally lost on how to solve g(x)=2x^2+3x-1 to find the y and x-...

Math - Please show the solutions! 1.) x+y-2(2x-3y) 2.) x+y/2 - 3x-y/4 + x-5y/8 3...

Rational Expression - (x+1/2x-1 - x-1/2x+1) * (2x-1/x - 2x-1/x^2) (x+1/2x-1 - x-...

Trigonometry - Which expression is equal to (6x^3+10x^2-4x+10)/(3x-1)? 1.) 2x^2+...

Algebra - I have worked this and checked it and it does not come out true any ...